Dari Song Osong Lombhung hingga Rampa’ Naong Bringin Korong - Muniri, Muniri; Aziz, Nur Chotimah; Mahsun, Mahsun; Shobri, Ach.; Hafid, Hafid (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2025)
This study examines three philosophies of life among the Madurese people—Song Osong Lombhung, Mon Soghi-Pasoghe’, and Rampa’ Naong Bringin Korong—as models of local wisdom that reflect the values of love and tolerance in Islam. This study aims to reveal the philosophical meanings of these proverbs and their relevance to the principles of Islam Nusantara. The method employed is local hermeneutics with a qualitative-interpretative approach to interpret Madurese symbols, language, and cultural practices within their social context. The findings indicate that Song Osong Lombhung emphasizes family solidarity, Mon Soghi-Pasoghe’ fosters social responsibility, and Rampa’ Naong Bringin Korong describes universal harmony. Together, these three form a value structure ranging from micro-level solidarity to cosmic love, aligning with the concept of rahmatan lil ‘alamin. This study concludes that Madurese local wisdom can serve as a model of contextual Islamic praxis that reinforces moderation, compassion, and social tolerance in Indonesia.